Development and optimization of a continuous flow ester reduction with LiAlH4 in the synthesis of a key intermediate for a PI3Kδ inhibitor (CPL302415). Issue 5 (24th February 2023) - Michałek, Stanisław; Maj, Anna M.; Gurba-Bryśkiewicz, Lidia; Maruszak, Wioleta; Zagozda, Marcin; Ochal, Zbigniew; Dubiel, Krzysztof; Wieczorek, Maciej
Abstract : Highly productive (11.3 g h −1 ) continuous flow LAH ester reduction in the synthesis of a new PI3Kδ inhibitor (CPL302415). Comparison of the efficiency and selectivity of various reduction methods (catalytic with stoichiometric and flow with batch). Abstract : Herein we present the development of highly productive and chemoselective ester reduction in a continuous flow system with lithium aluminum hydride (LAH) at mild temperature. The reaction was utilized for the reduction of an important precursor in the synthesis of a new PI3Kδ inhibitor (CPL302415), which is now under evaluation for the treatment of systemic lupus erythematosus. The productivity and the selectivity of the flow LAH reduction were compared with those of batch reaction, as well those of Ru-catalyzed ester reduction. The reaction has a high space–time yield (1130 kg h −1 m −3 ). The process was optimized using a design of experiments (DoE) approach.